Análisis de la eficiencia del biogás generado por el biodigestor Solar Cities en el campus CEASA, Período 2021-2022. - Andrade Estévez, Erika Nicole (2022)
The objective of this research report was to determine the efficiency of the bio-gas (methane) generated by a Solar Cities bio-digester located at the CEASA Campus. For which an initial diagnosis of the bio-digester was carried out. Subsequently, pig manure was used as a substrate for its operation, which was obtained from the CEASA Campus hatchery. The methodology for the generation of bio-gas was established concerning the time of permanence, temperature, and substrate type; the bio-gas's characterization was determined by employing a gas chromatography study, and its efficiency was determined based on research carried out on the flame color test. This bio-digester is designed to utilize the waste energetically and nutritionally, employing anaerobic decomposition. For its operation, a bibliographic investigation was carried out, and it was established as an initial load of 300 L of the substrate, with an input pH of 7.8, Nitrogen 25.69 %, Total Solids 42.44%, Volatile Solids 23.12 %, data obtained from the analysis of the manure. Within the results obtained in the gas chromatography in 56 days, 18% of methane was obtained, which is the gas that favors combustion; in the flame test, a yellow flame was obtained, which denotes the poverty of the bio-gas. In the second analysis, a percentage of 21.12% of methane was established; it was also concluded that the bio-gas generated does not comply with the necessary characteristics to supply the LPG applications. Finally, it is recommended to redesign the bio-digester model and periodically analyze the substrate's pH.